Experimental analysis of liquid movements in automotive fuel tanks. (2017) - Andreozzi, Assunta; Matteo, Luigi Di; Fortunato, Francesco
Nowadays, a complex activity is taking place to enhance design and validation of automotive fuel tanks. It includes track tests, new bench tests and fluid-dynamic simulations. The target is to prevent issues with vapour pressure build up and fuel spill to vapour canister, operating as early as possible in the design process. A new test bench has been developed by Moog Inc. based on Fiat Chrysler Automobiles (FCA) specification and experience, which allows simulating vehicle accelerations using a combination of tank motion and tilt on all axes. Accelerometric measurements have been conducted. A comparison between results obtained by means of the '8-DOF' innovative test bench (also called 'Fuel Tank Test System') and the ones obtained by means of a simpler '6-DOF' bench has been carried out. Moreover, the experimental results are compared with the ones obtained when the fuel tank is mounted on a vehicle running on a test track.